Prestasi Sanggar Rumah Gadang Sebagai Sebuah Organisasi Seni Pertunjukan Di Nagari Cupak Kabupaten Solok: Kajian Terhadap Tata Kelola Organisasi - Della Natasia Gunita Piska; Indrayuda Indrayuda (FBS Universitas Negeri Padang, 2020)
This research aims to describe and explain the governance of the organization of Rumah Gadang Dance Art in managing the order well to be able to achieve achievement both national and international so that it remains exist and survive to date. This type of research is qualitative research with a descriptive method. The main instrument in this research is its own researchers and assisted with supporting instruments such as notebooks, note taking tools, video cameras, photo cameras, and tape recorders. The data types in this study are primary data and secondary data. Data collection techniques are conducted by way of library studies, observation, interviews, documentation. The steps for analyzing data are data reduction, data presentation and withdrawal of conclusions. The results showed that the governance of the organization run by Sanggar Rumah Gadang can run well so that it produces good achievements. The research is included in a line organization (a form of organization where direct authority delegation is vertically and completely from leadership to its subordinates). The advantage of the line organization, all decisions can be resolved directly because in a particular situation the leader becomes one of the main targets in problem solving. Disadvantages of the line organization, if there is an issue or problem can not be resolved quickly because the leader is not in place. Thus the governance of the line Oganisasi to solve the problem or problems in the workshop, the head of the workshop became the first person to complete and resolve the issue.